Delayed diagnosis of ankylosing spondylitis in a Japanese population. Issue 3 (3rd May 2016) - Nakashima, Yasuharu; Ohishi, Masanobu; Okazaki, Ken; Fukushi, Jun-Ichi; Oyamada, Akiko; Hara, Daisuke; Doi, Toshio; Akasaki, Yukio; Yamada, Hisakata; Iwamoto, Yukihide
Abstract: Objectives : This study was conducted to evaluate the period from symptom onset to diagnosis of ankylosing spondylitis (AS) in Japanese patients and to examine possible reasons for delayed diagnosis. Methods : Seventy-two consecutive patients with AS were studied. Diagnostic delay was defined as the gap between the first spondyloarthropathic symptom and diagnosis of AS according to the modified New York criteria. Results : The mean patient ages at disease onset and diagnosis were 25.6 ± 11.3 and 33.3 ± 13.2 years old, respectively, resulting in diagnostic delay of 6.7 years. The number of medical institutions to which patients were referred before diagnosis was 2.4, and orthopedic surgeons were most commonly visited (62%). Non-specific low back pain or lumbar spondylitis (33%) and degenerative arthritis (28%) were the primary diagnoses preceding that of AS. Absence of articular symptoms significantly correlated with diagnostic delay. The patients with disease onset on year 2000 or later had significantly shorter periods until diagnosis than those before 2000 (3.6 vs. 7.5 years). Conclusions : The present study showed a marked diagnostic delay among Japanese patients with AS. Although it has been improved, continuing medical education focusing on inflammatory back pain in adolescent is required for early diagnosis of AS.